ReaxFF molecular dynamic simulation of primary and secondary reactions involving in sub-bituminous coal pyrolysis for tar production - Qian, Yanan; Zhan, Jin-Hui; Xu, Wei; Han, Zhennan; Liu, Xiaoxing; Xu, Guangwen (Carbon resources conversion, 2021)
[Display omitted] •ReaxFF MD is performed to understand the chemical behaviors of sub-bituminous coal pyrolysis.•Atomic-level quantitative relationship is clarified between bond breakage and products generation.•The primary generation and secondary upgrading mechanisms of tar are revealed. ReaxFF molecular dynamic simulation combined with experimental verification was performed to understand the overall reaction mechanism, especially the primary and secondary reactions involving in tar formation of sub-bituminous coal pyrolysis. Quantitative relationship at atomic level is clarified between bond breakage of functional groups and products generation, revealing that the amount and order in forming each product are subject to the number of corresponding functional groups and their bond energies respectively. The primary breakage of –C–O– and –C–C– bridge-bonds present in initial coal macromolecular generates molecular of heavy tar, whereas heavy tar can be converted into light tar through cracking side chain of aromatic rings and cyclic hydrocarbons at increased pyrolysis temperatures. At very high temperatures the cracking of short-chain hydrocarbons and residual atoms connecting to aromatic rings further occurs to generate light tar and gas. The remaining aromatic-ring fragments of heavy tar are likely cross-linked to form char. Furthermore, the simultaneous evolution tendency of tar yield and tar quality under different pyrolysis temperatures and heating rates is obtained at molecular level. For obtaining high yield and quality of tar, appropriately high temperature as well as suitable heating rate are needed to compromise the high yield of primary tar and high quality of secondarily upgraded products.